DESAIN MESIN PRODUKSI SANTAN SISTEM SENTRIFUGAL KAPASITAS 10 LITER/ JAM - Darwin Hendri; Herdi Susanto; Al Munawir (universitas teuku umar, 2020)
Coconut processing that still uses traditional methods, of course this is not efficient considering the long time of extortion and also requires a lot of energy for extortion. The purpose of this research is to design and manufacture centrifugal system coconut milk squeezer integrated with the grating process. The research method is carried out by the calculation of the main components of the machine and followed by component design using software. The results of this study explain that the design of coconut milk production machines with a power of 0.746 Kw using a 1 Hp power motor with 2850 rpm rotation, tube capacity of 10 liters per hour, tube torque in 25,812 Nm, shaft diameter 20 mm, clutch diameter 21 mm, bearing diameter 21 mm . The results of the design of coconut milk production machines with dimensions of length 600 mm, width 600 mm, and height 1200 mm Keywords— Coconut, coconut milk, component design, centrifugal force.